2004
DOI: 10.1074/jbc.m407962200
|View full text |Cite
|
Sign up to set email alerts
|

Deficiency of ABCA1 Impairs Apolipoprotein E Metabolism in Brain

Abstract: ABCA1 is a cholesterol transporter that is widely expressed throughout the body. Outside the central nervous system (CNS), ABCA1 functions in the biogenesis of high-density lipoprotein (HDL), where it mediates the efflux of cholesterol and phospholipids to apolipoprotein (apo) A-I. Deficiency of ABCA1 results in lack of circulating HDL and greatly reduced levels of apoA-I. ABCA1 is also expressed in cells within the CNS, but its roles in brain lipid metabolism are not yet fully understood. In the brain, glia s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
290
0
3

Year Published

2005
2005
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 342 publications
(308 citation statements)
references
References 84 publications
15
290
0
3
Order By: Relevance
“…The ABCA1 protein has a wide tissue distribution (Wellington et al 2002), but has been most studied in peripheral tissues. Recent studies have shown that deficiency of ABCA1 in the brain leads to a specific decrease in APOE levels (Hirsch-Reinshagen et al 2004;Wahrle et al 2004). Interestingly, ABCA1 shares a commonality with APOE in that it appears to be involved in Ab metabolism (Fukumoto et al 2002); this is supported by evidence suggesting a relationship between cholesterol metabolism and Ab metabolism (Simons et al 1998(Simons et al , 2001Kojro et al 2001).…”
Section: Introductionsupporting
confidence: 49%
See 1 more Smart Citation
“…The ABCA1 protein has a wide tissue distribution (Wellington et al 2002), but has been most studied in peripheral tissues. Recent studies have shown that deficiency of ABCA1 in the brain leads to a specific decrease in APOE levels (Hirsch-Reinshagen et al 2004;Wahrle et al 2004). Interestingly, ABCA1 shares a commonality with APOE in that it appears to be involved in Ab metabolism (Fukumoto et al 2002); this is supported by evidence suggesting a relationship between cholesterol metabolism and Ab metabolism (Simons et al 1998(Simons et al , 2001Kojro et al 2001).…”
Section: Introductionsupporting
confidence: 49%
“…That ABCA1 can directly influence Ab has been demonstrated (Fukumoto et al 2002), and more recent evidence suggests that ABCA1 also interacts with APOE in the CNS (Hirsch-Reinshagen et al 2004). In the present study, we suggest that genetic variants of ABCA1 may influence CSF Ab 1-42 levels, possibly reflecting its involvement with Ab metabolism.…”
Section: Discussionmentioning
confidence: 99%
“…The apoprotein/lipid ratio of lipoprotein particles can markedly influence properties such as receptor binding (Narita et al, 2002) and interactions with other molecules such as Ah (LaDu et al, 1994(LaDu et al, , 1995Tokuda et al, 2000). Importantly, two recent studies demonstrate that if apoE is poorly lipidated in the CNS due to the absence of the protein ATP-binding cassette transporter A-1 (ABCA1), apoE particles are rapidly metabolized in the brain resulting in levels that are 2% of normal in the CSF and b20% of normal in the cortex (Hirsch-Reinshagen et al, 2004;Wahrle et al, 2004). Thus, studying apoE derived from astrocyte cell lines that are lipidated by the cellular machinery possessed by these cells is likely be very useful to better model apoE's effects and interactions in the CNS.…”
Section: Discussionmentioning
confidence: 99%
“…There is some evidence that apoE isoforms may differ in their function in regard to cholesterol transport and efflux (Michikawa et al 2000;Gong et al 2002;Rapp et al 2006), although not all studies show this (Hirsch-Reinshagen et al 2004). Thus the roles of apoE isoforms in brain cholesterol metabolism require further investigation.…”
Section: Lrp1 and Ldlr In Cellular And Brain Ab Metabolismmentioning
confidence: 99%